2023
DOI: 10.5187/jast.2022.e72
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementary feeding on the production traits, carcass and meat quality of Jamuna basin lambs

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported. Funding sourcesState funding sources (grants, funding sources, equipment, and supplies). Include name and number of grant if available.Funded by Krishi Gobeshona Foundation (KGF) under the ministry of Agriculture, Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…Ash percentage were insignificant in different treatments, genotype and T*G having value 1.19, 1.03, 0.89 and 1.04% in T 0 , T 1 , T 2 and T 3 and 1.17, 0.92 and 1.02 in JBL, BRL and CBL. Hossain et al (2023) observed ash percentage found significantly lower (p<0.001) in four treatments compared to control group which were not similar with this study might be due to the stress condition.…”
Section: Effect Of Different Level Of Concentrate On Proximate Compon...contrasting
confidence: 65%
See 2 more Smart Citations
“…Ash percentage were insignificant in different treatments, genotype and T*G having value 1.19, 1.03, 0.89 and 1.04% in T 0 , T 1 , T 2 and T 3 and 1.17, 0.92 and 1.02 in JBL, BRL and CBL. Hossain et al (2023) observed ash percentage found significantly lower (p<0.001) in four treatments compared to control group which were not similar with this study might be due to the stress condition.…”
Section: Effect Of Different Level Of Concentrate On Proximate Compon...contrasting
confidence: 65%
“…The ADG was 57.39, 59.80 and 58.15 g/d in all treatments of JBL respectively according to which was close to present study in terms of JBL part. Level of concentrate feeding showed a significant difference (p<0.0001) on the final body weight and ADG in different treatments (Hossain et al, 2023;Barman et al, 2017;). A higher ADG was found in T 2 and T 3 but there was no statistical difference.…”
Section: Comparison Of Productive Performances Of Jbl Brl and Cbl At ...mentioning
confidence: 90%
See 1 more Smart Citation
“…These sheep are capable of bi-annual lambing and multiple births, and they are divided into three types based on regional basis: Jamuna basin, Barind, and Coastal belt indigenous sheep (Rashid et al, 2013;Hossain et al, 2018). Sheep farming is an important source of income for rural households and plays a significant role in poverty alleviation and employment generation in Bangladesh (Hossain et al, 2023a(Hossain et al, , 2023b(Hossain et al, and 2023c). The rearing system of sheep plays a crucial role in determining the growth and carcass traits of the animals.…”
Section: Introductionmentioning
confidence: 99%
“…Even the same breed can have different quality and taste characteristics depending on individual muscles ( Kumar et al, 2021 ; Lee et al, 2023b ; Won et al, 2023 ). Feeding management ( Hossain et al, 2023 ; Kim et al., 2023a ), slaughter weight, slaughtering processes ( Hwang et al, 2022 ; Oh et al, 2022 ), and processing methods ( Ismail et al, 2022 ; Lee et al., 2023a ) can also influence meat quality and taste characteristics. Therefore, exploring how primary determinants of meat quality change according to these factors and what mechanisms are involved can increase the possibility of high-quality meat production.…”
Section: Introductionmentioning
confidence: 99%